Development of Maths Booklet Media for Primary School Students - Armayanti, Ayuk; Nasution, Ismail Saleh (research, training and philanthropy institution Natural Aceh, 2024)
This research focuses on the development, validity, and practicality of booklet-based teaching materials for mathematics subjects, specifically on equivalent fractions. Following the Research and Development (R&D) model, which incorporates the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design stages, this research aims to create effective learning aids. The assessment of the developed Booklet showed high validity and practicality. The material expert assessment rated it